ASSESSMENT OF IMMUNOREACTIVITY DISORDER IN CHRONIC HEART FAILURE OF VARIOUS ETIOLOGIES - Adaxamov I. I.; Usmanova D. N.; Bektasheva G. M. (Scholars Digest Publishing, 2024)
Despite the development of special recommendations for the treatment of patients with CHF, the total number of hospitalizations and the frequency of early readmissions in this condition has not decreased, but tends to increase. All this leads to the search for new methods of diagnosis and therapy of CHF. According to a number of researchers [Mustafina D.M., 2001, El Sherif W.T., El Tooney L.F., Meki A.R., Abdel Moneim A., 2005] immune changes can play a key role in the pathogenesis of CHF. But in order to understand the contribution of immune mechanisms to the development of complications in coronary heart disease, it is necessary to compare this nosology with each other, where immune disorders play a key role. The available data suggest that cytokines play an important role in the pathogenesis of inflammation in CHF of ischemic and non-ischemic etiology. However, the mechanisms of inflammation development involving cytokines have not been disclosed, and the features of the relationship of inflammatory mediators with other parts of the immune system in CHF of various etiologies have not been established.
Keywords: antimyocardial autoantibodies, alatate aminotransferase, angiotensin II receptor antagonists, aspartate aminotransferase, dilated cardiomyopathy, endothelial dysfunction.